L'allegoria dell'amante in un sonetto di Gaspara Stampa - Wojtynek-Musik, Krystyna (Romanica Silesiana)
Krystyna Wojtynek-Musik analyses the allegory of the sun and the beloved in the sonet by Gaspara Stampa, paying attention to the formation of a series of meanings overlapping themselves, deriving from the literal sense. Keywords: Italian poetry; Gaspara Stampa’s lyrical poetry; allegory; poetic image; motif of the sun